Assisting Africa: a critical analysis of technical assistance in low carbon development practice - du Toit, Michelle (School of African and GenderStuds, Anth and Ling, 2019)
Climate change mitigation efforts are increasingly forming part of the agendas of African nations, particularly since the inclusion of voluntary targets for these countries within the United Nations Framework Convention on Climate Change (UNFCCC) Paris Agreement of 2015. This focus towards the mitigation of greenhouse gas emissions, together with the need to achieve development objectives, has become combined in the practice of ‘low carbon development’ within developing countries. Technical assistance programmes have been set up to support the achievement of low carbon development, and these activities typically flow from the global North to Africa. However the power structures and flows of benefit that underlie these practices have not been the subject of much enquiry and are largely occluded within the climate change mitigation community of practice. With the inclusion of climate change mitigation targets for developing countries together with a direct call for increased capacity building within the Paris Agreement, the volume of technical assistance support focused towards Africa is likely to increase. As such the need to consider what effective technical assistance, that is both equitable and appropriate to the African context, might look like becomes a priority. This study engages with these issues. By considering the literature arising from decolonial studies and development theory together with bringing to the fore the perceptions of African climate change mitigation professionals, it provides a critical analysis of the tacit assumptions that are legitimated within the technical assistance practice in climate change mitigation. The study finds that current modes of technical assistance practice within low carbon development continues to entrench the hegemonic nature of knowledge of the global North, and perpetuates the placement of Africa in a position of extraversion towards the North, assuming African government and climate change practitioners as lacking in knowledge and expertise. The study advocates for a more equal and bilateral flow of knowledge between the two regions in order for African nations to faster and more effectively reach the twin goals of development and mitigation within Africa. It considers the lack of the critical theories of decolonial studies and development theory in climate change scholarship (particularly the absence of African voices in the debate) and brings these alternative voices and theories into low carbon development technical assistance practice.